Low-thermal-conductivity micro-foaming door sealing material, preparation method and door sealing strip
By using materials such as PVC resin and other materials combined with low thermal conductivity microfoaming door sealing materials with organic expandable microspheres, the problem of difficult to reduce the thermal conductivity of refrigerator door seals is solved, and better insulation performance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411800117.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
AI Technical Summary
Existing refrigerator door seals have difficulties in reducing thermal conductivity, especially due to the high price of silica aerogels and poor compatibility of hollow glass microbeads with substrates, resulting in performance being affected.
Low thermal conductivity micro foam door sealing material is used, which consists of PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, fillers and dispersing compatibility agents. The organic expandable microspheres include spherical plastic cores composed of thermoplastic acrylic polymer shell and alkane gas. The foaming effect is achieved by softening the shell and expanding the core when heated.
While ensuring the reliability of the door seal performance, it significantly reduces the thermal conductivity of the door seal, improves the insulation performance of the door seal, avoids the problems of uneven bubble cells, cracking and poor rebound, and ensures good mechanical properties.
Smart Images

Figure CN119463383A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of foaming technology, and in particular to a low thermal conductivity micro-foamed door sealing material, a preparation method and a door sealing strip. Background Art
[0002] Refrigerator door seals are mainly used to seal the gap between the refrigerator door and the refrigerator body to maintain the temperature and humidity inside the refrigerator. Refrigerator door seals are usually made of soft polyvinyl chloride or other low-temperature resistant, corrosion-resistant, and aging-resistant materials, and have good elasticity and sealing properties.
[0003] As a component of refrigerator sealing and insulation, refrigerator door seals play an insulating role and are one of the key factors affecting refrigerator energy consumption. Door seal leakage accounts for 15%-20% of the total refrigerator leakage, and the proportion will continue to rise as the overall refrigerator insulation effect improves. The refrigerator door seal can improve the thermal insulation performance of the door seal by optimizing the material and airbag structure, thereby reducing the leakage of cold air in the box and reducing the power consumption of the refrigerator. Among them, the conventional way to reduce the thermal conductivity of the refrigerator door seal itself is to add low thermal conductivity materials such as silica aerogel and hollow glass microspheres during the door seal production process.
[0004] However, silica aerogel is relatively expensive, and hollow glass microspheres have poor compatibility with the refrigerator door seal substrate, which has a significant impact on the performance of the refrigerator door seal. Summary of the invention
[0005] The present application provides a low thermal conductivity micro-foamed door seal material, a preparation method and a door seal strip, which reduce the thermal conductivity of the door seal and improve the thermal insulation performance of the door seal while ensuring the reliability of the door seal performance.
[0006] In a first aspect, the present application provides a low thermal conductivity micro-foamed door sealing material, comprising: PVC resin, a plasticizer, a stabilizer, a lubricant, organic expandable microspheres, a filler, and a dispersing compatibilizer;
[0007] The organic expandable microspheres include an outer shell and an inner core, wherein the outer shell is a thermoplastic acrylic polymer and the inner core is a spherical particle plastic composed of alkane gas;
[0008] The raw materials of the low thermal conductivity micro-foamed door sealing material include, by weight, 100 parts of PVC resin, 60-80 parts of plasticizer, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer.
[0009] Optionally, the PVC resin includes at least one polyvinyl chloride resin, and the degree of polymerization of the polyvinyl chloride is 1300-2100.
[0010] Optionally, the stabilizer is one or more of zinc stearate, calcium stearate, hydrotalcite, pentaerythritol, phosphite, and antioxidant.
[0011] Optionally, the plasticizer is one or more of dioctyl terephthalate, trioctyl trimellitate, dioctyl sebacic acid, dinonyl cyclohexane 1,2-dicarboxylate, and epoxy soybean oil.
[0012] Optionally, the filler is one or more of barium sulfate, talc, wollastonite, and calcium carbonate, and the particle size of the filler is 1-10 nm.
[0013] Optionally, the dispersed compatibilizer is one or more of a silane coupling agent and a titanate coupling agent.
[0014] Optionally, the diameter of the organic expandable microspheres is 10-45 μm.
[0015] In a second aspect, the present application provides a method for preparing a low thermal conductivity micro-foamed door sealing material, comprising:
[0016] Add 100 parts by weight of PVC resin, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer into a high-speed mixing pot, and mix at a first speed for 5 minutes;
[0017] Adding 60-80 parts of plasticizer into the high-speed mixing pot, during which the plasticizer is added into the high-speed mixing pot, the high-speed mixing pot is operated at a second speed;
[0018] Raise the temperature of the high-speed mixing pot to 100° C. and mix at the first speed for 3 minutes;
[0019] Raising the temperature of the high-speed mixing pot to 120° C.-160° C., and mixing at the second speed for 30 minutes to obtain a mixed powder;
[0020] The mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foamed door sealing material.
[0021] Optionally, the first rotational speed is less than the second rotational speed.
[0022] In a third aspect, the present application provides a door seal for use in a refrigerator, wherein the door seal is formed by extruding the low thermal conductivity micro-foamed door seal material described in the first aspect through an extruder.
[0023] It can be seen from the above technical scheme that the present application provides a low thermal conductivity micro-foam door sealing material, a preparation method and a door sealing strip, wherein the low thermal conductivity micro-foam door sealing material includes PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersed compatibilizer; the organic expandable microspheres include an outer shell and an inner core, the outer shell is a thermoplastic acrylic polymer, and the inner core is a spherical granular plastic composed of alkane gas; the raw materials of the low thermal conductivity micro-foam door sealing material include 100 parts of PVC resin, 60-80 parts of plasticizer, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersed compatibilizer in weight. By using organic expandable microspheres as foaming agents, during the preparation process, when heated to a certain temperature, the thermoplastic shell softens, the gas in the shell expands, the volume of the foaming agent increases, and the structure of the organic expandable microspheres will not be destroyed, thereby achieving the foaming effect. Since organic expandable microspheres have no pores, they avoid the shortcomings of uneven pores, pore rupture, and poor pore resilience. The complete spherical structure ensures good mechanical properties. At the same time, the thermal conductivity of organic expandable microspheres is low, which reduces the thermal conductivity of the door seal while ensuring the reliability of the door seal performance and improves the thermal insulation performance of the door seal. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0025] Figure 1 A flow chart of a method for preparing a low thermal conductivity micro-foamed door sealing material provided in an embodiment of the present application;
[0026] Figure 2 This is a schematic diagram of the organic expandable microsphere structure and foaming provided in the embodiments of the present application. DETAILED DESCRIPTION
[0027] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.
[0028] Refrigerator door seals are mainly used to seal the gap between the refrigerator door and the refrigerator body to maintain the temperature and humidity inside the refrigerator. Refrigerator door seals are usually made of soft polyvinyl chloride or other low-temperature resistant, corrosion-resistant, and aging-resistant materials, and have good elasticity and sealing properties.
[0029] As a sealing and heat-insulating component of the refrigerator, the refrigerator door seal plays a role in heat insulation and is one of the key factors affecting the energy consumption of the refrigerator. The cold leakage of the door seal accounts for 15%-20% of the cold leakage of the whole machine, and the proportion will continue to rise as the heat preservation effect of the whole refrigerator is improved. The heat insulation performance of the refrigerator door seal can be improved by optimizing the structure of materials and airbags, thereby reducing the leakage of cold air in the box and reducing the power consumption of the refrigerator.
[0030] In some embodiments, low thermal conductivity materials such as silica aerogel and hollow glass microspheres are added during the preparation of the door seal to reduce the thermal conductivity of the door seal. However, silica aerogel is relatively expensive, and hollow glass microspheres have poor compatibility with the refrigerator door seal substrate, which has a significant impact on the performance of the refrigerator door seal.
[0031] Therefore, while ensuring the reliability of the door seal performance, the thermal conductivity of the door seal is reduced and the thermal insulation performance of the door seal is improved. Some embodiments of the present application provide a low thermal conductivity micro-foamed door seal material, wherein the low thermal conductivity micro-foamed door seal material is composed of PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer.
[0032] Among them, Figure 2 As shown, the organic expandable microspheres include an outer shell and an inner core, the outer shell is a thermoplastic acrylic polymer, and the inner core is a spherical particle plastic composed of alkane gas; the diameter of the organic expandable microspheres is 10-45μm. Among them, the outer shell of the organic expandable microspheres is a thermoplastic acrylic polymer, which has good heat resistance and mechanical properties, and can soften and form a stable outer shell when heated. The inner core is a spherical particle composed of alkane gas, which expands when heated, thereby increasing the volume of the entire microsphere. The expanded organic expandable microspheres have good thermal insulation properties, which will reduce the thermal conductivity of the door seal. At the same time, the organic expandable microspheres have a lower density after expansion, which is conducive to reducing the density of the door seal.
[0033] The raw materials of the low thermal conductivity micro-foam door sealing material include, by weight, 100 parts of PVC resin, 60-80 parts of plasticizer, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer.
[0034] Specifically, in the above embodiment, the PVC resin includes at least one polyvinyl chloride resin, and the degree of polymerization of the polyvinyl chloride is 1300-2100. During the processing, the performance of the PVC resin can be improved by adding different additives. For example, in the present application, the performance of the PVC resin is improved by adding plasticizers, fillers, dispersants, and organic expandable microspheres.
[0035] Specifically, the stabilizer is one or more of zinc stearate, calcium stearate, hydrotalcite, pentaerythritol, phosphite, and antioxidant. Among them, the role of the stabilizer is to prevent the PVC resin from degrading, changing color and other adverse reactions during processing and use. Stabilizers such as zinc stearate and calcium stearate can react with trace metal ions in the PVC resin to form stable complexes, thereby protecting the PVC resin from oxidation and hydrolysis. Stabilizers such as hydrotalcite and pentaerythritol have multiple functions, which can not only improve the thermal stability of PVC resin, but also improve its processing performance. Stabilizers such as phosphite and antioxidant are mainly used to inhibit the oxidative degradation process of PVC resin and extend the service life of the product.
[0036] The plasticizer is one or more of dioctyl terephthalate, trioctyl trimellitate, dioctyl terephthalate, dicyclohexane 1,2-dicarboxylic acid dinonyl fat, and epoxy soybean oil. The main function of the plasticizer is to increase the flexibility and processing fluidity of the PVC resin, making it easier to process and shape. For example, plasticizers such as dioctyl terephthalate and trioctyl trimellitate can reduce the glass transition temperature of the PVC resin, making it remain soft at room temperature. In addition, the plasticizer can also improve the compatibility between the PVC resin and other raw materials.
[0037] The filler is one or more of barium sulfate, talcum powder, wollastonite, and calcium carbonate, and the particle size of the filler is 1-10nm. The function of the filler is to improve the hardness, strength and wear resistance of the door seal, while reducing the cost. Fillers such as barium sulfate, talcum powder, wollastonite, and calcium carbonate can improve the mechanical strength and thermal stability of PVC resin and extend the service life of the product. The particle size of the filler is 1-10nm, and the particle size of the filler is small, so it can be better dispersed in the PVC resin.
[0038] The dispersing compatibilizer is one or more of a silane coupling agent and a titanate coupling agent. The main function of the dispersing compatibilizer is to improve the compatibility between the PVC resin and other raw materials so that each raw material can be evenly dispersed to form a uniform mixture. For example, dispersing compatibilizers such as silane coupling agents and titanate coupling agents can chemically react or physically adsorb with the PVC resin and other raw materials to form a stable interface layer.
[0039] Adding organic expandable microspheres can improve the thermal conductivity of PVC to enhance the thermal insulation performance of the door seal.
[0040] In some embodiments, Figure 1 As shown, the embodiment of the present application provides a method for preparing a low thermal conductivity micro-foamed door sealing material, comprising:
[0041] S100: Add 100 parts by weight of PVC resin, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer into a high-speed mixing pot, and mix at a first speed for 5 minutes.
[0042] S200: Add 60-80 parts of plasticizer into the high-speed mixing pot.
[0043] Wherein, during the process of adding the plasticizer into the high-speed mixing pot, the high-speed mixing pot operates at the second speed.
[0044] S300: Raise the temperature of the high-speed mixing pot to 100° C. and mix at the first speed for 3 minutes.
[0045] S400: raising the temperature of the high-speed mixing pot to 120° C.-160° C. and mixing at a second speed for 30 minutes to obtain a mixed powder;
[0046] S500: The mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foamed door sealing material.
[0047] Specifically, PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to a high-speed mixing pot, and stirred at a low speed of 60 r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320 r / min.
[0048] When all the plasticizers are added to the high-speed mixer, the temperature of the high-speed mixer is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixer is raised to 120-160°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foamed door sealing material.
[0049] The first rotational speed is a low rotational speed, the second rotational speed is a high rotational speed, and the first rotational speed is lower than the second rotational speed.
[0050] The technical solution of the present invention will be further described below through multiple embodiments.
[0051] Embodiment 1
[0052] A low thermal conductivity micro-foam door seal material, comprising PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer. The raw materials of the low thermal conductivity micro-foam door seal material include 100 parts of PVC resin, 80 parts of plasticizer, 5 parts of stabilizer, 1 part of lubricant, 20 parts of organic expandable microspheres, 20 parts of filler and 2 parts of dispersing compatibilizer by weight.
[0053] A method for preparing a low thermal conductivity micro-foam door sealing material comprises the following steps:
[0054] PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to the high-speed mixing pot, and stirred at a low speed of 60r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320r / min.
[0055] After all the plasticizers are added to the high-speed mixing pot, the temperature of the high-speed mixing pot is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixing pot is raised to 120°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foam door seal material. After obtaining the low thermal conductivity micro-foam door seal material, the low thermal conductivity micro-foam door seal material can be put into an extruder for extrusion molding to obtain a low thermal conductivity micro-foam door seal.
[0056] Embodiment 2
[0057] A low thermal conductivity micro-foam door seal material, comprising PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer. The raw materials of the low thermal conductivity micro-foam door seal material include 100 parts of PVC resin, 80 parts of plasticizer, 5 parts of stabilizer, 1 part of lubricant, 30 parts of organic expandable microspheres, 20 parts of filler and 2 parts of dispersing compatibilizer by weight.
[0058] A method for preparing a low thermal conductivity micro-foam door sealing material comprises the following steps:
[0059] PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to the high-speed mixing pot, and stirred at a low speed of 60r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320r / min.
[0060] After all the plasticizers are added to the high-speed mixing pot, the temperature of the high-speed mixing pot is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixing pot is raised to 130°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, granulated by a pelletizer, and then extruded by an extruder to obtain a low thermal conductivity micro-foam material. After obtaining the low thermal conductivity micro-foam door seal material, the low thermal conductivity micro-foam door seal material can be put into an extruder for extrusion molding to obtain a low thermal conductivity micro-foam door seal.
[0061] Embodiment 3
[0062] A low thermal conductivity micro-foam door seal material, comprising PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer. The raw materials of the low thermal conductivity micro-foam door seal material include 100 parts of PVC resin, 80 parts of plasticizer, 5 parts of stabilizer, 1 part of lubricant, 50 parts of organic expandable microspheres, 10 parts of filler and 2 parts of dispersing compatibilizer by weight.
[0063] A method for preparing a low thermal conductivity micro-foam door sealing material comprises the following steps:
[0064] PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to the high-speed mixing pot, and stirred at a low speed of 60r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320r / min.
[0065] After all the plasticizers are added to the high-speed mixing pot, the temperature of the high-speed mixing pot is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixing pot is raised to 140°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foam door seal material. After obtaining the low thermal conductivity micro-foam door seal material, the low thermal conductivity micro-foam door seal material can be put into an extruder for extrusion molding to obtain a low thermal conductivity micro-foam door seal.
[0066] Embodiment 4
[0067] A low thermal conductivity micro-foam door seal material, comprising PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer. The raw materials of the low thermal conductivity micro-foam door seal material include 100 parts of PVC resin, 80 parts of plasticizer, 5 parts of stabilizer, 1 part of lubricant, 0 parts of organic expandable microspheres, 60 parts of filler and 2 parts of dispersing compatibilizer by weight.
[0068] A method for preparing a low thermal conductivity micro-foam door sealing material comprises the following steps:
[0069] PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to the high-speed mixing pot, and stirred at a low speed of 60r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320r / min.
[0070] After all the plasticizers are added to the high-speed mixer, the temperature of the high-speed mixer is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixer is raised to 150°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foam door seal material. After obtaining the low thermal conductivity micro-foam door seal material, the low thermal conductivity micro-foam door seal material can be put into an extruder for extrusion molding to obtain a low thermal conductivity micro-foam door seal.
[0071] Embodiment 5
[0072] A low thermal conductivity micro-foam door seal material, comprising PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer. The raw materials of the low thermal conductivity micro-foam door seal material include 100 parts of PVC resin, 80 parts of plasticizer, 5 parts of stabilizer, 1 part of lubricant, 0 parts of organic expandable microspheres, 0 parts of filler and 2 parts of dispersing compatibilizer by weight.
[0073] A method for preparing a low thermal conductivity micro-foam door sealing material comprises the following steps:
[0074] PVC resin, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer are added to the high-speed mixing pot, and stirred at a low speed of 60r / min for 5 minutes. Then, plasticizer is slowly added, for example, 2 parts of plasticizer are added per minute. During the process of adding plasticizer to the high-speed mixing pot, the high-speed mixing pot is stirred at a high speed of 320r / min.
[0075] After all the plasticizers are added to the high-speed mixing pot, the temperature of the high-speed mixing pot is raised to 100°C, and stirred at a speed of 60r / min for 3 minutes, and then the temperature of the high-speed mixing pot is raised to 160°C, and stirred at a speed of 320r / min for 30 minutes to obtain a mixed powder. Finally, the mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foam door seal material. After obtaining the low thermal conductivity micro-foam door seal material, the low thermal conductivity micro-foam door seal material can be put into an extruder for extrusion molding to obtain a low thermal conductivity micro-foam door seal.
[0076] When the door seal strip is made of the low thermal conductivity micro-foamed door seal material of each of the above embodiments, the physical parameters of the door seal strip are specifically shown in Table 1:
[0077] Table 1 Physical parameters of door seals
[0078]
[0079] Among them, Example 1, Example 2 and Example 3 are control groups of physical parameters of door seals with different weight portions of organic expandable microspheres added. When more organic expandable microspheres are added, the thermal conductivity of the prepared door seal will gradually decrease, and the hardness will also gradually decrease. In Example 4 and Example 5, no organic expandable microspheres are added. The thermal conductivity of the door seal prepared according to the ratio of Example 4 and Example 5 is higher. Therefore, when preparing the material of the door seal, adding a certain amount of organic expandable microspheres can significantly reduce the thermal conductivity of the door seal.
[0080] In addition, according to the hardness parameters in Examples 1 to 5, the content of organic expandable microspheres will also affect the hardness of the door seal. When more organic expandable microspheres are added, the hardness of the prepared door seal is lower, and the tolerance of the door seal is improved. When the door seal prepared by adding organic expandable microspheres is used in a refrigerator, the sealing performance of the door seal can be improved, the thermal conductivity of the door seal can be reduced, and the thermal insulation performance of the door seal can be improved.
[0081] However, it can be seen from Examples 1, 2 and 3 that when more organic expandable microspheres are added, the tensile strength and elongation of the prepared door seal are smaller. Therefore, when preparing the door seal, it is necessary to appropriately limit the amount of organic expandable microspheres added.
[0082] In some embodiments, the present application provides a door seal, which is applied to a refrigerator. The door seal is formed by extruding the low thermal conductivity micro-foamed door seal material provided by the above embodiment through an extruder.
[0083] It can be seen from the above technical scheme that the present application provides a low thermal conductivity micro-foam door sealing material, a preparation method and a door sealing strip, wherein the low thermal conductivity micro-foam door sealing material includes PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersed compatibilizer; the organic expandable microspheres include an outer shell and an inner core, the outer shell is a thermoplastic acrylic polymer, and the inner core is a spherical granular plastic composed of alkane gas; the raw materials of the low thermal conductivity micro-foam door sealing material include 100 parts of PVC resin, 60-80 parts of plasticizer, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersed compatibilizer in terms of weight. By using organic expandable microspheres as foaming agents, during the preparation process, when heated to a certain temperature, the thermoplastic shell softens, the gas in the shell expands, the volume of the foaming agent increases, and at the same time, the structure of the organic expandable microspheres will not be destroyed, thereby achieving the foaming effect. Since organic expandable microspheres have no pores, they avoid the shortcomings of uneven pores, pore rupture, and poor pore resilience. The complete spherical structure ensures good mechanical properties. At the same time, the thermal conductivity of organic expandable microspheres is low, which reduces the thermal conductivity of the door seal while ensuring the reliability of the door seal performance and improves the thermal insulation performance of the door seal.
[0084] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.
Claims
1. A low thermal conductivity micro-foamed door sealing material, characterized in that: include: PVC resin, plasticizer, stabilizer, lubricant, organic expandable microspheres, filler and dispersing compatibilizer; The organic expandable microspheres include an outer shell and an inner core, wherein the outer shell is a thermoplastic acrylic polymer and the inner core is a spherical particle plastic composed of alkane gas; The raw materials of the low thermal conductivity micro-foamed door sealing material include, by weight, 100 parts of PVC resin, 60-80 parts of plasticizer, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer.
2. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The PVC resin includes at least one polyvinyl chloride resin, and the polymerization degree of the polyvinyl chloride is 1300-2100.
3. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The stabilizer is one or more of zinc stearate, calcium stearate, hydrotalcite, pentaerythritol, phosphite and antioxidant.
4. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The plasticizer is one or more of dioctyl terephthalate, trioctyl trimellitate, dioctyl sebacic acid, dinonyl cyclohexane 1,2-dicarboxylate, and epoxy soybean oil.
5. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The filler is one or more of barium sulfate, talc, wollastonite, and calcium carbonate, and the particle size of the filler is 1-10 nm.
6. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The dispersed compatibilizer is one or more of a silane coupling agent and a titanate coupling agent.
7. The low thermal conductivity micro-foamed door sealing material according to claim 1, characterized in that: The diameter of the organic expandable microspheres is 10-45 μm.
8. A method for preparing a low thermal conductivity micro-foamed door sealing material, characterized in that: include: Add 100 parts by weight of PVC resin, 4-7 parts of stabilizer, 0.3-1.2 parts of lubricant, 20-50 parts of organic expandable microspheres, 10-30 parts of filler, and 1-3 parts of dispersing compatibilizer into a high-speed mixing pot, and mix at a first speed for 5 minutes; Adding 60-80 parts of plasticizer into the high-speed mixing pot, during which the plasticizer is added into the high-speed mixing pot, the high-speed mixing pot is operated at a second speed; Raise the temperature of the high-speed mixing pot to 100° C. and mix at the first speed for 3 minutes; Raising the temperature of the high-speed mixing pot to 120° C.-160° C., and mixing at the second speed for 30 minutes to obtain a mixed powder; The mixed powder is put into an extruder for melt extrusion, and granulated by a pelletizer to obtain a low thermal conductivity micro-foamed door sealing material.
9. The method for preparing a low thermal conductivity micro-foamed door sealing material according to claim 8, characterized in that: The first rotation speed is lower than the second rotation speed.
10. A door seal, used in a refrigerator, characterized in that: The door seal is formed by extruding the low thermal conductivity micro-foamed door seal material according to any one of claims 1 to 7 through an extruder.